Concept and Determinants of Quality in Higher Education. A Survey Conducted amongst Spanish University Lecturers. Concepto y Determinantes de la Calidad de la Educación Superior. Un Sondeo de Opinión entre Profesores de Universidades Españolas. - Antonio Cardona Rodríguez; Miren Barrenetxea Ayesta; Juan José Mijangos del Campo; Jon Olaskoaga Larrauri (Arizona State University, 2009)
This article presents a portion of the results obtained through a survey and about different aspects related to quality in higher education conducted with University lecturers in Spain specialized in the areas of Economics and Business during the period February-April 2008. After providing a brief description of the main features of our research this article examines the ideas about quality in higher education as well as who are the agents involved in it. This article includes a brief analysis of some of the most relevant results about the impact of actions aimed at the improvement of quality of higher education, and it analyses the opinions about different ways to understand quality. En este artículo presentamos parte de los resultados de un sondeo realizado entre profesores universitarios españoles de las áreas de economía y empresa entre febrero y abril de 2008 sobre diversos aspectos ligados a la calidad de la educación superior. Se exponen fundamentos sobre la calidad en la educación superior y sobre los agentes que intervienen en ella. Se describe brevemente nuestro trabajo de investigación y se presenta un breve análisis de algunos de los resultados más relevantes en cuanto a la incidencia de diversos factores en la mejora de la calidad de la educación superior, y en cuanto a la opinión sobre diversas formas de entender esa calidad.